Optimalisasi Fitur YouTube Sebagai Media Pemberdayaan Ekonomi Lembaga Muslimah Wahdah Islamiyah - Johan Hendri Prasetyo; Fajar Sarasati; Luky Fabrianto; Rizky Ade Safitri; Hamzah Ali Abdullah; Henny Yuwanda; Regina Sephiani; Alfin Nur Laili Salma (Perbanas Institute, 2023)
The increasingly massive development of the digital era has forced various profit and non-profit industries to be able to adapt, especially in digital marketing, and the South Jakarta Muslimah Wahdah Islamiyah Institute is no exception. One of the problems faced by Muslimah Wahdah Islamiyah in South Jakarta is the lack of utilization of the YouTube feature as an institutional marketing medium. This is of course a problem that needs to be addressed immediately, considering that South Jakarta Muslimah Wahdah Islamiyah is a da'wah institution that has various programs, such as da'wah, education, economics, social, and health. Therefore, Lecturers and Students of the Digital Business Study Program held community services to optimize YouTube features with the aim of helping South Jakarta Muslimah Wahdah Islamiyah in empowering the economy for the organization and its members.